Stent evaluation in low-dose coronary CT angiography: Effect of different iterative reconstruction settings - Wüst, Wolfgang; May, Matthias; Scharf, Michael; Layritz, Christian; Eisentopf, Jasmin; Ropers, Dieter; Pflederer, Tobias; Uder, Michael; Achenbach, Stephan; Lell, Michael (Journal of Cardiovascular Computed Tomography, 2013)
Background: Different iterative reconstruction (IR) techniques compensate increased noise from lower tube current-time product settings, yet the differences between IR settings remain unclear. Objective: Aim of this study was to test whether different IR settings have a clinically relevant influence on image quality and on the diagnostic accuracy of low-dose CT angiography in patients with a stent. Methods: Forty-two patients with 73 coronary stents were prospectively enrolled. Data were acquired with dual-source CT, and images were reconstructed with standard filtered back projection (FBP) and raw data-based IR with different settings (I3, I4, I5). Quantitative parameters, including CT-attenuation, noise, signal-to-noise ratio, contrast-to-noise ratio, as well as the presence of in-stent stenosis > 50% were determined. All patients had invasive angiography as reference standard. Results: Mean effective dose was 0.32 ± 0.02 mSv. Image noise decreased significantly compared with FBP (I3= 29%; I4= 38% and I5= 45%), whereas signal-to-noise and contrast-to-noise ratios increased significantly (all IR settings P <.01). Subjective image quality was superior with all IR settings (P < .01). FBP sensitivity, specificity, positive predictive value, and negative predictive value were 83%, 71%, 36%, and 96% per stent compared with 100%, 76%, 44%, and 100%, respectively, in IR reconstructions independent of the IR setting applied. Conclusion: In low-dose coronary CT angiography, higher IR settings significantly improved subjective and objective image quality but had no effect on accuracy. © 2013 Society of Cardiovascular Computed Tomography.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Cardiac CT; Coronary stents; Iterative reconstruction; Low dose; SAFIRE